Male and Female Information Systems Students' Communication Styles in Academic Discussions: A Sociolinguistic Study at Batuta University Medan - Dwi Suci Amaniarsih (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
Communication styles play a significant role in shaping students' participation and interaction during academic discussions. Gender has been identified as one of the social factors that may influence communication behaviors in educational settings. This study aimed to investigate the communication styles of male and female students during academic discussions in the Information Management Study Program at Batuta University Medan. The study employed a qualitative descriptive case study design involving 30 students, consisting of 15 male students and 15 female students. Data were collected through classroom observations, audio-recorded discussions, and semi-structured interviews. The data were analyzed using thematic analysis to identify communication patterns and interactional features. The findings revealed that male students tended to employ more direct, assertive, and competitive communication styles, as reflected in their higher frequency of initiating discussion topics, presenting arguments, and interrupting conversations. Female students, on the other hand, demonstrated more collaborative and supportive communication styles through the use of clarification questions, supportive feedback, and cooperative interaction strategies. Despite these differences, both groups actively participated in academic discussions and contributed valuable ideas. The study concludes that communication styles are influenced not only by gender but also by educational context and classroom culture. The findings contribute to sociolinguistic research on gender and communication and provide pedagogical implications for promoting inclusive and effective classroom interaction in higher education.